SOCIAL CAPITAL AND VALUE CREATION: THE ROLE OF INTRAFIRM NETWORKS. - Tsai, W.; Ghoshal, S. (Academy of Management Journal, 1998)
Your use of the JSTOR archive indicates your acceptance of JSTOR's Terms and Conditions of Use, available at